Pembelajaran Pendidikan Agama Islam (PAI) dalam Membentuk Nilai Toleransi Beragama di SMPN 1 Cepu - Moh. Na`im (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
Religion is a source of the value of tolerance and has a very close relationship to enter into one's soul. To form human beings who are religious and have the value of tolerance in themselves, directed education is needed. The purpose of this study was to determine the learning process of Islamic religious education in forming the value of tolerance in the SMPN 1 Cepu environment namely knowing the strategy, implementation and evaluation of Islamic religious education teachers. This research is a field research, Data was collected by using observation, interview and documentation techniques. The results of this study indicate that: first , the Islamic religious education strategy in shaping the value of religious tolerance in the SMPN 1 Cepu environment is carried out well and effectively by applying it through subjects and social activities so as to foster mutual respect both with teachers and fellow friends, both fellow Muslims and Muslims. non-muslim. The second implementation is through programs in the curriculum, especially regarding religion, such as traveling tadarus, dhuhur prayers in congregation, then talent development such as social assistance, visiting sick hospitals, spreading flowers on HIV AIDS day and memorizing prayers according to religious beliefs. each. Third evaluation which conducted teacher PIE in the development of tolerance values already covers whole aspect evaluation, that is cognitive, affective and psychomotor.